Nitrogen and Phosphorus Nanocomposite Fertilizers: Synthesis, Particle Size and Matrix Effects - Giroto, Amanda Soares (2018)
With high agricultural productivity, is necessary a chemical fertilization of soil, and nitrogen and phosphorus are the macronutrients indispensable for plants. In this sense, the current demand for fertilizer requires that more rational methods of using these compounds be developed, seeking strategies to increase and control the solubility of the sources used, as well as avoiding immobilization, coalescence or agglomeration processes, which would compromise availability during the application process. Therefore, the central proposal of this work was to study how the decrease of the size of phosphate particles through the dispersion of their agglomerates would influence their solubilization kinetics. For this, the work was started investigating different materials that could act as dispersing matrix. One of the main characteristics of this work was to work with dispersing matrices that would also be a source of nutrient, in this case, nitrogen. Thus, the preparation of the urea: urea-formaldehyde matrix was studied by the simple method of mixing and melting the solid phase materials. In order to obtain materials with different degrees of polymerization of urea, unlike the literature, where only the production of a rigid (fully polymerized) matrix of urea-formaldehyde in the liquid phase was found. From the results of solubilization in water and even by the incubation tests in the soil, it was verified that the degree of polymerization of the urea strongly influenced its availability in both media. Since the bond between urea and formaldehyde is a strong bond, another material is sought to interact with urea but is poorer than the former. Thus, starch has emerged as an excellent candidate for matrix formation. However, when using this source the final N contents are very low when one thinks of fertilizer. In order to increase the final N content in the matrix melamine was added in the structure since the reactions of urea-melamine are already well known in the literature, but together with the starch, it is still a material little studied for use as fertilizer. Interestingly, melamine changed the morphology of TPSUr (thermoplastic starch: urea) composites, making them more homogeneous and rigid. Also, by greenhouse studies, it was observed that melamine had no nutritional role during the experiment period, but strongly modified the kinetics of urea availability in order to be more efficient than pure urea. Studying the possible matrices, it was begun the study of the dispersion of the phosphate particles in two different matrices, using the simplest matrices for the first tests. Thus pure urea and thermoplastic starch: urea were used as the two dispersing sources. The results demonstrated that the dispersion method was efficient to maintain the particles at the nanoscale consequently having a higher solubilization in the aqueous medium. In these tests, it was also verified that the morphology of the composites was the main characteristic for the better availability of both nutrients. And to close the work, soil experiments were carried out. From these results it was observed that the hydrolysis of the structural urea, modified the local pH of the composites, disfavoring the complexation of the soluble phosphorus in leaving it more available in the soil compared to the commercial source.